Cross-border Cooperation in French-German Non-profit Organisations - Kloth, Melina (Jihočeská univerzita, 2020)
This master's thesis pursues the questions of how the firefighters are organised in Germany and France and of what consequences the Covid-19 sanitary crisis had on their cross-border cooperation in the Upper Rhine region.The qualitative research has been carried out in the context of an internship at the central public administration for the fire and rescue services of the French department of Bas-Rhin. In total, three semi-structured interviews have been conducted with German voluntary and professional firefighters and two narrative interviews have been done with French administrative and operational staff of the training institution. Light has been shed on the terms cross-border cooperation, civil security, risk management and the communication of risks, organisational structures and culture as well as on the European funding programme INTERREG and the current situation of projects involving firefighters.
Cross-border Cooperation in French-German Non-profit Organisations
La Coopération Transfrontali?re des Acteurs Publics de la Sécurité Civile
Keywords: cross-border cooperation; INTERREG; firefighters; civil security; Covid-19; management of crisis situations; France; Germany; Upper-Rhine; cross-border cooperation; INTERREG; firefighters; civil security; Covid-19; management of crisis situations; France; Germany; Upper-Rhine